Urgensi Partisipasi Pesantren sebagai Pusat Edukasi dan Moderasi Islam dalam Percepatan Pariwisata Halal di Indonesia - Galuh Widitya Qomaro (Proceedings of Annual Conference for Muslim Scholars, 2018)
This study aims to identify the importance of Pesantren's role, socially and psychologically, as one of the main pillars of halal tourism development in Indonesia. Beside fashion, food and finance trends, halal tourism is also one of the mainstay sectors in the world's halal industry. Halal tourism is an added value for tourism industry in Indonesia. Pesantren, as one of the stakeholders in the halal tourism industry pentahelix, plays an important role in many things, such as: identifying halal tourism destinations, raising public awareness in processing food, choosing travel services and concepts, and determining the method of payment of travel services. Pesantrens should also be involved in the educational process on Islamic business ethics, formal or non-formal training for the halal tourism industry implementers, and also residents of halal tourist areas for shariah daily-style concept. This research is conducted with qualitative approach. Data collection uses literature study through documents, both written and electronic documents that support the writing process. This study shows that Pesantren should have participated comprehensively in the Indonesian halal tourism industry so that with maximum management will greatly contribute to the achievement of Indonesia's halal tourism internationalization program.